Special: An interview with Robert Prus: His Career, Contributions, and Legacy as an Interactionist Ethnographer and Social Theorist - Kleinknecht, Steven (Qualitative Sociology Review, 2007)
I have used an extended, open-ended interview with Robert Prus as a means with which to consider his contributions to ethnographic research and social theory. Given the range of his scholarship, a fairly detailed listing of the topics covered in the interview is presented at the outset. In addition to (a) considering Robert Prus’s own career as a scholar, attention is given to (b) his involvements in symbolic interaction as a field of study, (c) ethnographic research as a mode of inquiry, (d) generic social processes as a realm of theorizing about the nature of human group life, and (e) some specific ethnographies on which he has worked as well as (f) his critiques of both positivist and postmodernist scholarship and (g) his involvements in tracing the development of pragmatist social thought from the classical Greek era to the present time and even more recent thoughts on (h) the sociology of Emile Durkheim and (i) public sociology.